UNMASKING FIGURATIVE LANGUAGE OF TAYLOR’S SWIFT MEGA HIT SONG “ANTI-HERO" - Dwi, Zila; Vionisa, Evatul; Ainni, Nurul; Sintiasari, Cindy; Irmayani, Irmayani (MEDIA DIDAKTIKA, 2024)
This article explores the presence and impact of figurative language in Taylor Swift's music, focusing on the lyrical depth and artistic nuances found in her songs. It highlights the use of metaphors, similes, and personification in Swift's songwriting, emphasizing their ability to evoke emotions, create vivid imagery, and enhance the narrative power of her compositions. The study draws upon existing research on figurative language in music to provide a comprehensive understanding of how Swift's use of these literary devices enhances her lyrical and artistic expression. The article also presents a research methodology for analyzing the figurative language in Swift's songs and offers a detailed description of the findings and their implications. By examining specific examples from Swift's songs, the article aims to uncover the underlying artistic and communicative strategies used by the artist and shed light on the impact of her figurative language on the audience's interpretation and emotional response.